Molecular taxonomy of Hyrcanian Alnus using nuclear ribosomal ITS and chloroplast trnH-psbA DNA barcode markers. Issue 1 (2nd January 2016) - Colagar, Abasalt Hosseinzadeh; Yousefzadeh, Hamed; Shayanmehr, Fatemeh; Jalali, Seyed Gholamali; Zare, Habib; Tippery, Nicholas P.
Abstract : The taxonomy and phylogeny of Hyrcanian Alnus (eight taxa) were investigated using sequence data from the nuclear ribosomal ITS and the chloroplast trnH-psbA intergenic spacer. The mean nucleotide compositions of the ITS region were completely equal for two main Hyrcanian taxa, and the ITS1 region had fewer variable sites than the ITS2 region. Two relatively distinct types of ITS2 were identified for two main clades of Hyrcanian Alnus, the A . subcoradata complex and A . glutinosa . Two recently described species, A. dolichocarpa and A. djavanshirii, did not show any diagnostic sites and had a similar pattern with A . subcordata . Three recognized subspecies of A . glutinosa were distributed in the A . incana complex. In the analysis of trnH-psbA sequence data, the three subgenera of Alnus were poorly resolved relative to one another. Alnus glutinosa had minimal sequence divergence from A. incana and A. tenuifolia, and A. subcordata had a minimum distance from A. cordata and A. orientalis . A maximum pairwise distance also was observed between Hyrcanian species ( A. glutinosa and A. subcordata ) with A. pendula and A. sieboldiana, respectively. Ultimately, the molecular phylogeny of Alnus based on two DNA barcode markers was not congruent with recent morphological classifications, so additional DNA markers should be explored for identifying Alder taxa in the Hyrcanian forest.